(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The aim of the work was a comprehensive study of the clinical efficacy and changes in the local immune response during conservative rehabilitation after surgical treatment of leukoplakia of the oral mucosa using local keratoplasty. The dynamics of subjective complaints, clinical manifestations, as well as immune status indicators were assessed: the level of secretory IgA , IL-1β, IL-6 and TNF-α. The data obtained indicate a pronounced regenerative, antiseptic and immunomodulatory effect of the drug, which confirms its high clinical value in this pathology.